تأثير استخدام الفيديو على نتائج تعليم النّحو لدى الطّلّاب تخصّص في الدّين في المدرسة الثّانويّة الحكوميّة 2 بوكيت تنجي - Hasanah, Uswatun; Wahyuni, Wira; Febrianta, Rita; Sa’adiah, Hurriyatus (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by lower student learning outcomes because the learning methods being implemented still use traditional methods and the media used are still few so that students are less interested in participating in learning, causing many students to score low. This research is a semi-experimental design research. The design format used is Nonequivalent Control Group Desain. The research community in this research reached 66 people consisting of two classes. The research sample consists of 33 individuals from the experimental category and 33 people from the control category. The data analysis method used is normal state testing, homogeneity testing, and hypothesis testing. It can be concluded that there is a significant impact on the outcome of students' education using the video medium and using traditional methods. This was reinforced by the hypothesis test score of 0.05, and the result of Sig was < 0.05 (0,001 < 0.05) and t hitung > t tabel t (2,348 < 3,391) so that it can be concluded that there is an effect of video means on the result of teaching grammar in experimental class students compared to the traditional method in the control classroom.